GEOGRAPHY SKILLS DOMAIN TAXONOMY - Fahrudi Ahwan Ikhsan; Fahmi Arif Kurnianto; Bejo Apriyanto; Elan Artono Nurdin (Geosfera Indonesia, 2018)
This study aims to explain the geography student skills domain. The focus of this research is the domain of geography skills possessed by students. The research method with the a qualitative approach. Subjects were students of Jember University geography education consisting of 2 men and 2 women with indicators of academic ability value of the national geography exam results. Data collection techniques by observation and interview. Data were analyzed using the processing unit, categorization and interpretation of data. The findings show that the skills of geography for prospective teachers of geography and geographers to be possessed composed as follows: 1st level thinking skills geography (space, phenomena, location and place, region, environment, coordinate, and humans), level 2 skills of analysis geography (scale, distribution, patterns of interaction, interrelation, connectivity, corologi, descriptions, and agglomeration), and level 3 skills of geographic applications (mapping/cartography, remote sensing, geographic information systems, surveying and mapping of the area, and Global Position systems (GPS). This level difference is used to distinguish the use of knowledge and application of the science of geography. Keywords: Students of geography education, geography Skills Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License